Vocational education and training in Sub-Saharan Africa : current situation and development - Eicker, Friedhelm [Herausgeber]; Haseloff, Gesine [Herausgeber]; Lennartz, Bernd [Herausgeber] (Bertelsmann, 2017)
"In einigen Ländern der südlichen Saharazone (SSA) steigt die Nachfrage nach Fachkräften. Ein durchgängiges System der beruflichen Aus- und Fortbildung ist in der Region noch nicht etabliert. In dem Tagungsband tragen die Autor/innen Praxiswissen zur Situation der beruflichen Bildung in den afrikanischen Subsahara-Staaten zusammen. Sie stellen Konzepte für die Entwicklung eines Systems zur beruflichen Ausbildung vor und geben einen Überblick über Strategien und Vorhaben verschiedener Länder und Institutionen. Die Beiträge entstanden im Rahmen eines Symposions zum Status quo und zur Perspektive der beruflichen Aus- und Fortbildung. Es fand im August 2016 in Namibia mit Teilnehmer/innen aus Wissenschaft und Praxis der Subsaharastaaten, Europa, Australien und Asien statt." Session 1: Vocational Education and Training (VET) - Basics for teaching and research in Vocational Education and Training at Universities; Session 2: Establishment of a VET system with focus on Further Education - presentation of ideas on the motivation and establishment of a Further Education system (FES), especially in Universities in Sub-Sahara Africa; Session 3: What are concepts or conditions of success for a networked VET learning and teaching (oriented on competence, working practice, flexible, etc.) and especially for a networked Further Education system in VET? (Verlag, BIBB-Doku)

"There is a rising demand for specialist workers in several countries of Sub-Saharan Africa (SSA). The area still lacks a consistent system of professional training and further education. The conference transcript comprises practical knowledge collected by the authors to depict the current state of professional training within the Sub-Saharan African countries. The paper also introduces the reader to concepts for the development of a professional training system and provides an overview of the strategies and plans of different countries and institutions. The included articles were written within the framework of a symposium on the status quo and the perspective of professional training and further education. This gathering took place in Namibia in August 2016 and brought together researchers and business actors from the Sub-Saharan states, Europe, Australia and Asia." (Publisher, BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.3.1 Afrika; I 1.1 Systemberatung; Berufsbildung; Subsahara-Afrika; Systemberatung [Berufsbildung]; Internationale Zusammenarbeit; Internationaler Vergleich; Fachkräftebedarf; Ausbilder; Qualifizierung